On the Outlook : Figures of the Messianic. - Thomas Crombez and Katrien Vloeberghs (Cambridge Scholars Publishing, 2007)
This volume explores the traditional and contemporary modes and stakes of messianic thinking in its close interaction with both previous and actual political contexts and theoretical discourses. In the past decades, philosophers and political thinkers rep.